INCREASING FORMULATE AND TEST CONJECTURE MATH COMPETENCE AND SELF CONFIDENCE IN USING THE DISCOVERY LEARNING TEACHING MATH - Sylvia Rabbani; Tatang Herman (PrimaryEdu : Journal of Primary Education, 2017)
The main problem of this study is the lack of ability to formulate a conjecture of mathematics students in grade 5 elementary schools, lack of ability to test the conjecture of mathematics students in grade 5 elementary school and a low attitude of self-confidence of students Primary 5. This study uses quantitative and qualitative approach and methods of quasi and descriptive. The study population was the fifth-grade elementary school students in District Ciparay Bandung regency. The sample consisted of 66 students divided into 33 classes of students in the various groups of experiment V-A  and 33 students in the class V-B as the control group. The instrument used comprising written tests on multiplication and division of fractions, and ratio and scale, attitude scale questionnaire of self-confidence, observation, and interviews. Quantitative analysis was performed on average pretest and posttest ability to compose and mathematical conjecture test using the t-test and Mann Whitney. Qualitative analysis was also conducted on the attitude scale questionnaire score self-confidence confirmed by observation and interview. The results pointed to an that mathematics learning by using discovery learning can improve students' mathematical formulate the conjecture. Learning mathematics using discovery learning can also improve students' mathematical test conjecture. The self-confidence of students in the experimental class was obtained using discovery learning math learning is good.